2020
DOI: 10.1007/s00394-020-02341-x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of dietary intake, nutrition knowledge and hydration status of Gaelic Football players

Abstract: Purpose To assess the dietary intake, nutrition knowledge and hydration status of Irish Gaelic footballers. Method One hundred and sixty-eight male club/county level Irish Gaelic footballers (median [IQR]; age 23 years [20.0, 27.0]; height 1.79 m [1.74, 1.84]; body mass 78.0 kg [73.5, 84.8]) participated in this cross-sectional study. Dietary intake was assessed using a 4-day semi-quantitative food record, with the application of Goldberg cut-offs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 39 publications
4
32
0
Order By: Relevance
“…The overall SNK of players was poor (47.6%), and this is consistent with previous research on Gaelic games athletes [ 23 , 24 , 25 , 26 , 27 ], direct comparison of nutrition knowledge scores between studies can be difficult due to the use of different assessment tools. However, similar knowledge scores were observed for both female and male Gaelic footballers using an abridged version of the same questionnaire [ 23 , 26 ], while sub-elite Gaelic footballers reported lower levels of nutrition knowledge using the same question [ 24 ]. The difference between elite and non-elite players could be explained by the fact that the majority of elite players assessed in this study had access to a registered nutritionist/dietitian.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The overall SNK of players was poor (47.6%), and this is consistent with previous research on Gaelic games athletes [ 23 , 24 , 25 , 26 , 27 ], direct comparison of nutrition knowledge scores between studies can be difficult due to the use of different assessment tools. However, similar knowledge scores were observed for both female and male Gaelic footballers using an abridged version of the same questionnaire [ 23 , 26 ], while sub-elite Gaelic footballers reported lower levels of nutrition knowledge using the same question [ 24 ]. The difference between elite and non-elite players could be explained by the fact that the majority of elite players assessed in this study had access to a registered nutritionist/dietitian.…”
Section: Discussionsupporting
confidence: 88%
“…Athletes that demonstrated higher nutrition knowledge consume more fruit, vegetables and CHO rich foods than those with lower levels of nutrition knowledge [ 22 ]. Previous research has identified that both elite and sub-elite Gaelic football players demonstrated poor nutrition knowledge [ 23 , 24 , 25 ]. Similarly, elite female Gaelic games players and elite male hurlers demonstrated inadequate levels of nutrition knowledge [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a high proportion of athletes also had suboptimal vitamin A (38.7%), potassium (30.6%), zinc (25.8%), magnesium (19.4%) and calcium (12.9%). Preexercise hydration status (median urine specific gravity 1.010 [IQR 1.005, 1.017]) was significantly below the cut-off to represent dehydration (1.020) [19]. In five studies done on Australian athletes to evaluate and compare nutritional intake to current recommendations, the study participants were found to have low NK (answered only 51, 57, 54.5%, 46, 56.9% (professional athletes) /61.3% (semiprofessional athletes) of the Sports NK Questionnaire questions correctly, respectively) and their energy and nutritional intakes of macronutrients (carbohydrate and protein) and some micronutrients (calcium and iron) were incoherent with current recommendations [8,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 96%